Role of Opioid Ligands in the Irritable Bowel Syndrome - Enrico Corazziari (Canadian Journal of Gastroenterology)
Endogenous opioid peptides – enkephalins, beta-endorphin and dynorphins – are located in specific sites of the brain, the spinal cord, the autonomic ganglia and the enteric nervous system. Endogenous opioids participate in the regulation of nervous visceral afference and sensitivity as well as of several visceral motor function induced by the central nervous system and through the enteroenteric and the myoenteric reflexes. Their final effect on gut physiology is the net and harmonically balanced result of their binding to mu, delta and kappa opioid receptor subtypes. Exogenous opioid receptor ligands with different affinities for the opioid receptor subtypes have been effectively used to modify and normalize altered gut functions. Themureceptor agonists – morphine and, to a greater extent, the meperidine congeners diphenoxylate and loperamide – have been shown to slow gastrointestinal transit by their effects on the circular and longitudinal muscle of the intestine. Diphenoxylate and, more efficiently, loperamide, for the lack of any effect on the central nervous system, have been usefully employed in the treatment of diarrhea in irritable bowel syndrome (IBS) patients. Unlike the mu receptor agonists morphine and loperamide, which invariably stimulate colonic motility, trimebutine, which has almost equal affinity for mu, delta and kappa receptors, has no effect on normal colonic activity but reduces the abnormal increase in postprandial motor activity in IBS patients and accelerates slow large bowel transit in constipated patients. Opioid ligands can be usefully employed to normalize altered visceral sensitivity in IBS patients. The kappa receptor agonist fedotozine exerts its antinociceptive effect by acting on peripheral nerve endings of sensory vagal and nonvagal afferent pathways. Fedotozine has been shown to increase the threshold of perception to colonic distension in experimental conditions and to affect favourably symptoms of IBS in clinical trials.